PENGEMBANGAN AGRO WISATA DAN SENI BUDAYA DESA CIBURIAL KABUPATEN BANDUNG - Said Bambang Nurcahya; Nisrina Nisrina; Abna Maula Nur Bhaiti (Jurnal Pengabdian Kepada Masyarakat, 2022)
Currently the world economy is being shaken by the Covid 19 Pandemic, the Agricultural Sector is one of the commodities that can be the mainstay of an agricultural country like Indonesia to stabilize the national economy. Seeing this opportunity, it is not wrong if the development of agribusiness clusters or agro-techno parks is one of the promising commodities. However, the factor of land availability and the selection of the right agricultural business unit commodities are still a big consideration for agribusiness actors. Land which is the main capital in the development of agricultural production is increasingly difficult to obtain, while the demand for agricultural commodities continues to increase. The concept of developing an agro area is feasible to be developed to answer future challenges. In Ciburial Village there is a land owned by Mr. BJ.Habibie covering an area of ​​8,000 M2. The area is currently managed by the community to grow chilies, tomatoes and vegetables, but these individual cultivators do not produce anything that has added value for the land owner, and does not even provide welfare for the surrounding community. . From the results of a visit survey on an area of ​​8,000 m2, currently the land is planted with tubers, chili trees, tomatoes, banana trees by cultivators with an intercropping pattern. Keywords : Agrowisata, Seni budaya